DEPRESSION SYMPTOMS AMONG PREGNANT WOMEN IN ASIAN DEVELOPMENT COUNTRIES, 2012-2021: A SYSTEMATIC REVIEW (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the prevalence of depressive symptoms in pregnant women in developingcountries in Asia, period 2012-2021.Methods: A systematic review, conducting a search and synthesizing the results of studies ondepression in pregnant women in developing countries in Asia in the period 2012-2021.Results: 31 studies were included in the analysis. Among 34,657 pregnant women who participatedin the study, there were 6943 pregnant women with depression symptoms, accounting for 20.03%.Conclusion: The rate of depression symptoms among pregnant women was still high. It is necessaryto have appropriate intervention activities to improve the health status of pregnant women andnewborn babies.
Keywords: Depression, depressive symptoms, pregnancy, antenatal, the developing countries, Asia.